FILSAFAT ILMU: ONTOLOGI, EPISTIMOLOGI, DAN AKSIOLOGI - Ali, Afifah (Aqidah-ta: Jurnal Ilmu Aqidah, 2025)
In the field of philosophy, there are three main pillars that form the basis of the framework of thought, namely ontology, epistemology, and axiology. Ontology is concerned with the study of the existence and nature of reality, and questions what exists and how the relationships between these entities are. Meanwhile, epistemology discusses the theory of knowledge, investigating the nature, sources, and limitations of knowledge, and how humans gain an understanding of the world. Axiology focuses on values ​​and ethics, namely studying what is considered good or bad, and the basis for moral actions and decisions. These three schools of thought are interrelated and form a comprehensive worldview, influencing various fields of knowledge, including science and the humanities. Understanding the core of these three schools of thought is important for examining fundamental questions related to existence, knowledge, and the values ​​that guide human life. The purpose of this study is to investigate and analyze the three important dimensions in the philosophy of science, namely ontology, epistemology, and axiology, along with the existing major schools of thought, to build a comprehensive and integrated conceptual framework in understanding the foundations of science.